The Churchill sisters : the extraordinary lives of Winston and Clementine's daughters - Trethewey, Rachel (New York : St. Martin's Press, 2021)
Winston and Clementine Churchill's daughters each had a unique relationship with their famous father. Bright, attractive and well-connected, in any other family the Churchill girls - Diana, Sarah, Marigold and Mary - would have shone. But they were not in another family, they were surrounded by a clan of larger-than-life characters which often saw them overlooked. Marigold died too young to achieve her potential, the other daughters lived lives full of passion, drama and tragedy. Diana, intense and diffident; Sarah, glamorous and stubborn; Mary, dependable yet determined - each so different but each imbued with a sense of responsibility toward each other and their country. Far from being cosseted debutantes, these women were eyewitnesses at some of the most important events in world history.
Includes bibliographical references and index.
Keywords: Churchill, Winston, -- 1874-1965 -- Family; Churchill, Clementine, -- 1885-1977 -- Family; Churchill family; Churchill, Diana, -- 1909-1963.; Churchill, Sarah, -- 1914-1982.; Churchill, Marigold, -- 1918-1921.; Soames, Mary; Children of prime ministers -- Great Britain -- Biography; Sisters -- Great Britain -- Biography; Women -- Great Britain -- Biography